การพัฒนาชุดกิจกรรมทางคณิตศาสตร์ตามแนวคิดการใช้บริบทเป็นฐาน ร่วมกับการสร้างแบบจำลองทางคณิตศาสตร์ เพื่อส่งเสริมความสามารถในการเชื่อมโยงความรู้คณิตศาสตร์ และเจตคติต่อวิชาคณิตศาสตร์ของนักเรียนชั้นมัธยมศึกษาปีที่ 3 - ตั้งเก้าสกุล, สกล; ม้าคนอง, อัมพร (An Online Journal of Education, 2018)
The purposes of this research were 1) to develop the mathematical activity package by using context based approach and mathematical modelling and 2) to study the quality of the mathematical activity package by 1. comparing the mathematical connection abilities of students between before, during and after learning., 2. comparing mathematical connection abilities of students after learning with the criteria of 70%., 3. comparing the attitudes towards mathematics of students before and after learning., 4. studying development of the mathematical connection abilities of students learning from the activity package. The subjects were ninth grade students in Wattanothaipayap school, Chiang mai. The research instruments were mathematical activity package by using context based approach and mathematical modelling, mathematical connection abilities tests, interview and observation form and attitude towards mathematics inventory. The data were analyzed by using mean, standard deviation, t-test, one – way ANOVA and content analysis. The results of the study revealed that: 1) the mathematical activity package emphasizes on situations or real problems in life for students think and create mathematical models to solve the problems., 2) the mathematical connection abilities during and after learning were higher than before learning, after learning were higher than during learning, after learning were higher than the 70% criteria at a .05 level of significance. The attitudes towards mathematics after learning were higher than those before learning at a .05 level of significance., and the mathematical connection abilities of students were developed in positive direction.